The safety and effectiveness comparison of Delta Medical's PEEK interface screw and Endobutton and that of Smith & Nephew's in arthroscopic anterior cruciate ligament reconstruction: A multicenter prospective double-blind randomized controlled clinical trial - Peng Gao; Peng Gao; Minghao Yuan; Yongsheng Xu; Yufeng Wu; Xiaohang Lin; Yanlin Li; Shensong Li; Jing Wang; Jing Wang (Frontiers Media S.A., 2022)
BackgroundTo reduce the costs and financial burden in the ACLR treatment, we compare the early clinical outcomes and Magnetic Resonance Imaging (MRI) results of Delta Medical's PEEK (polyether ether ketone) interference screw and EndoButton with those of Smith & Nephew's PEEK interference screw and EndoButton in patients with arthroscopic anterior cruciate ligament reconstruction.MethodsA total of 104 patients in five different medical centers were randomly allocated into two groups: 1: Delta Medical's PEEK interference screw and EndoButton (53 patients); 2: Smith & Nephew's PEEK interference screw and EndoButton (51 patients). The modified Lysholm knee score, the laxity examination, and clinical and functional range of motion were evaluated at 3 and 6 months postoperatively. The clinical effective rate was calculated and classified as excellent and good at 6 months postoperatively. MRI examinations were performed at 3 and 6 months postoperatively to determine the healing process. Computerized tomography (CT) was performed at 2 weeks and 3 months postoperatively to evaluate the complications.ResultsSignificant improvements in knee function and functional scores were observed in both groups after surgery regardless of the fixation materials applied (P < 0.05). No differences were observed in the functional scores and range of motion. The assessments of Lysholm knee scores at 3 and 6 months produced no statistical differences (both P > 0.05). The clinical effective rate revealed no difference between the groups at 6 months postoperatively (non-inferiority analysis P = 0.0220). The differences of laxity examination between the groups were not statistically significant (Fisher's test, P = 0.6139, 0.2004, respectively). No significant differences in the functional range of motion were found at each follow-up time-point (P > 0.05). No major intra- or postoperative complications, such as infection, and vessel or nerve injury were observed.ConclusionsKnee function and functional scores were improved after ACLR in both groups, regardless of the PEEK interference screw and EndoButton applied. The difference in functional scores and range of motion were not significant in groups 1 and 2. Delta Medical's PEEK interference screw and EndoButton had a non-inferiority effect compared to Smith & Nephew's PEEK interference screw and EndoButton. Delta Medical's PEEK interference screw and EndoButton were suitable for arthroscopic ACLR.